2013
DOI: 10.1007/s11325-013-0820-9
|View full text |Cite
|
Sign up to set email alerts
|

Epworth sleepiness scale scores and adverse pregnancy outcomes

Abstract: There is an increased association between women with higher ESS and planned Cesarean delivery. Severe EDS was associated with gestational diabetes in pregnant women in a small sample size. Future studies in larger samples need to confirm the association of severe EDS and gestational diabetes and elucidate potential mechanisms of the links with adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 47 publications
1
29
0
5
Order By: Relevance
“…Sleep loss or self-imposed SSD during pregnancy may also impair glucose regulation given that women who sleep less have more opportunities to eat. Furthermore, sleepiness and fatigue, which are common conditions in pregnancy, are independently associated with insulin resistance [54•], resulting in increased risk of obesity [2]. Stress and fatigue due to inadequate sleep may also lead to comfort eating, physical inactivity and eventually obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep loss or self-imposed SSD during pregnancy may also impair glucose regulation given that women who sleep less have more opportunities to eat. Furthermore, sleepiness and fatigue, which are common conditions in pregnancy, are independently associated with insulin resistance [54•], resulting in increased risk of obesity [2]. Stress and fatigue due to inadequate sleep may also lead to comfort eating, physical inactivity and eventually obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Results from Bourjeily [54•] et al also have demonstrated that severe daytime sleepiness increases the risk of GDM in nonsnoring pregnant women, independent of confounders. These studies suggest that sleep has modulatory influences on glucose regulation regardless of time of day.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies during pregnancy have used a symptom-based approach, relying on either the patient or partner’s report of snoring, apnea, or excessive leg activity. 31,88,89 Several questionnaires are available (e.g. Berlin or Hawaii questionnaire, Epworth sleepiness scale).…”
Section: The Diagnosis Of Sleep Disordersmentioning
confidence: 99%
“…Berlin or Hawaii questionnaire, Epworth sleepiness scale). 31,34,35,37,42,44,46,48,49,88,90,91 The gold standard for the diagnosis of sleep disorders is polysomnography, in which the patient is studied and monitored continuously in a sleep laboratory. This modality consists of a comprehensive recording of biophysiologic parameters by electroencephalography, electrooculography, electromyography, electrocardiography, nasal and oral airflow as well as pulse oximetry.…”
Section: The Diagnosis Of Sleep Disordersmentioning
confidence: 99%
“…Yet whether women with sleep-disordered breathing and/or daytime napping are at risk for gestational diabetes is unknown. Using the Epworth Sleepiness Scale (ESS) which is a measure of daytime fatigue and surrogate marker of poor nocturnal sleep, Bourjeily et al [33] described a significant association between sleep and GDM in patients with a score >16 compared to those with an ESS of ≤16 which persisted after multiple adjustments (aOR, 6.82; 95% CI, 1.19–39.27). Finally, Reutrakul et al [28] noted that each hour of reduced sleep time was associated with a 4% increase in glucose levels following a 50-gram OGTT during the second trimester.…”
Section: Sleep and Glycemic Controlmentioning
confidence: 99%